Novel strategy of mixing MgO in CuO/water nanofluid for thermal conductivity improvement: Experimental study - J. Sathish Kumar; G. Senthilkumar; S. Ramachandran (Case Studies in Thermal Engineering, 2023)
The objective of the research is to address how polyhedron shaped MgO nanoparticles can solve the poor thermal conductivity issues due to spherical form of CuO nanoparticles. The novelty is the enhancement of thermal conductivity due to the combined effect of specific heat of MgO and two-step approach for the preparation of nanofluid. In the current study, the novel strategy for addition of fraction of MgO nanoparticles to improve the inferior thermal conductivity (TC) resulted due to agglomeration of CuO in water is addressed with proper experimental data. This novel approach was done with CuO/MgO weight ratio 7:3 and at volume fraction (VOF) of nanoparticles from 0.25 to 1.5 % in water from 30 to 55 °C. The present investigation resulted that marginal improvement in TC with a well defined contribution of nanoparticle in base fluid. Additionally, the outcome demonstrated that, particularly at higher temperatures, the thermal conductivity enhancement of nanofluid was proportional to both volume fraction and temperature. One such evidence was 12.5 % increase in TC at 55 °C and 1.5 % VOF. Likewise, the thermal conductivity's experimental result at various temperature and particle fraction was highlighted with proper literatures.